2011
DOI: 10.1371/journal.ppat.1002145
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Hypoxia and a Fungal Alcohol Dehydrogenase Influence the Pathogenesis of Invasive Pulmonary Aspergillosis

Abstract: Currently, our knowledge of how pathogenic fungi grow in mammalian host environments is limited. Using a chemotherapeutic murine model of invasive pulmonary aspergillosis (IPA) and 1H-NMR metabolomics, we detected ethanol in the lungs of mice infected with Aspergillus fumigatus. This result suggests that A. fumigatus is exposed to oxygen depleted microenvironments during infection. To test this hypothesis, we utilized a chemical hypoxia detection agent, pimonidazole hydrochloride, in three immunologically dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
250
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(269 citation statements)
references
References 80 publications
13
250
0
1
Order By: Relevance
“…By using heat maps to express fc, we observed that proteins involved in the glycolysis/gluconeogenesis, glyoxylate and TCA pathways have greater probe reactivity over time in HS culture than in minimal medium. The high reactivity of pyruvate decarboxylase pdc and alcohol dehydrogenase adh1 within these pathways is consistent with a switch from aerobic respiration to fermentation (65). High reactivity of enzymes within the gluconeogenesis pathway and TCA pathway is further evidence that ethanol is being used as a carbon source (75,76).…”
Section: Journal Of Biological Chemistry 33455supporting
confidence: 52%
“…By using heat maps to express fc, we observed that proteins involved in the glycolysis/gluconeogenesis, glyoxylate and TCA pathways have greater probe reactivity over time in HS culture than in minimal medium. The high reactivity of pyruvate decarboxylase pdc and alcohol dehydrogenase adh1 within these pathways is consistent with a switch from aerobic respiration to fermentation (65). High reactivity of enzymes within the gluconeogenesis pathway and TCA pathway is further evidence that ethanol is being used as a carbon source (75,76).…”
Section: Journal Of Biological Chemistry 33455supporting
confidence: 52%
“…This relative lack of molecular oxygen can be further amplified in pathological conditions, such as organ inflammation or ischaemia, and within solid tumours, due to damaged vasculature, compartmentalisation of infection, and high metabolic activity and oxygen requirements of pathogens and host cells. Hypoxia has been demonstrated in numerous pathological environments through in vitro and in vivo sampling: by microelectrode pO 2 measurement of wounds and venous ulcers [24]; by blood gas analysis of abscesses, a characteristic feature of staphylococcal infection [25]; by staining for hypoxia inducible factor (HIF), which increases exponentially below 6% oxygen, in chronic obstructive pulmonary disease [26]; by pimonidazole staining in pulmonary infection [27]; and by luminescence-based in vivo optical imaging in skin infection [28]. Interestingly, in a murine model of acute colitis, neutrophils actively contributed to the hypoxic microenvironment by depletion of molecular oxygen through NADPH oxidase activity and, hence, induced stabilisation of epithelial HIF [29].…”
Section: Relevance Of Hypoxia To Neutrophilsmentioning
confidence: 99%
“…10, the virulence levels of all three mutants were indistinguishable from that of the wt, indicating that both of these ERAD proteins are dispensable for virulence. Since inflammation has been reported to contribute to pathogenesis in this model (35), we considered the possibility that the reconstituting immune system could potentially mask an attenuated virulence phenotype for the ⌬hrdA ⌬derA mutant if the inflammatory response mounted against it was exaggerated. However, the mutant revealed no decrease in fungal growth relative to the wt in histopathologic sections of infected lung tissue, and comparable levels of inflammation were observed between strains (see Fig.…”
Section: Figmentioning
confidence: 99%